Analysis of the Influence of Digital Economy on Carbon Emissions - Li, Xiaoqin; Ao, Xiaolang (International Journal of Global Economics and Management, 2024)
As a new modern economic system, digital economy (DE) has been extensively applied in several industries owing to its low-carbon and green characteristics. This study examines the relationship between DE and carbon emissions (CE). We collected panel data for 30 provinces in China from 2003 to 2019 to study the influence of DE on CE. The results are as follows: (1) Fixed effects model analysis shows that DE presents an overturned U-shaped relationship that indicates increased CE initially and then a gradual decrease in them. (2) Heterogeneity analysis shows that the influence of DE on CE is different in various areas, and DE in the eastern area has the most conspicuous inhibition effect on CE. (3) Spatial model analysis reveals that DE has a remarkable spatial spillover effect on CE. The growth of a DE both locally and in neighborhoods can curb CE. The study’s results can help policymakers to devise policy recommendations that can reduce CE, which will help China to realize double carbon goal.